Adherence to smartphone-delivered antimicrobial prescribing guidelines in hospitals in Lao PDR: A stepped-wedge cluster randomized controlled trial - Vilada Chansamouth; Danoy Chommanam; Sue J. Lee; Susath Vongphachanh; Manivanh Vongsouvath; Sommay Keomany; Viladeth Paphasiri; Chanthala Phamisith; Siho Sengsavang; Phouvieng Douangdala; Khamsay Detleuxay; Sommana Rattana; et al. (PLOS Medicine, 2026)
Background Prescribing guidelines are a cornerstone of antimicrobial stewardship programs. Smartphone applications can increase access in low-and middle-income countries (LMICs). Following the release of the Lao national antimicrobial prescribing guidelines in 2021, this trial compared adherence to these guidelines delivered by a smartphone application versus the paper-based version among hospitalized patients and outpatients in six hospitals in Laos. Methods and findings An open cohort stepped-wedge cluster randomized controlled 3-step trial was conducted from 2021–2022. The intervention was a smartphone application-based prescribing guideline and antimicrobial stewardship (AMS) training. The reference was a paper-based version of the same guidelines. Adherence was defined as prescriptions using the correct antimicrobial(s) and correct dose based on the provided prescribing guidelines. The primary outcome was assessed via repeated point prevalence surveys (PPS) at ~4-month intervals. Data were analyzed using a mixed-effects regression model, accounting for time and clustering. Among 3,561 hospitalized patient prescriptions, overall guideline adherence was 17.0% (95% confidence interval or CI [15.0,19]) in the reference group, and 25.6% (95% CI [23.1,28.3]) in the intervention group. After accounting for time and cluster effects and adjusting for confounders (sequence of intervention, age, gender, prescribing indication, and hospital department), adherence did not differ by guideline delivery mode (adjusted odds ratio (aOR)=1.26 (95% CI [0.8,1.9]; p = 0.276). Similar findings were observed in outpatient settings (aOR = 0.91 (95% CI [0.7,1.1]; p = 0.406)). Outpatient adherence varied by time of intervention introduction, with the first group of hospitals exposed to the intervention showing higher odds of adherence (32.1% [302/940]; 95% CI [29.1,35.2]) compared with the last group (19.1% [241/1,261]; 95% CI [16.9,21.4]) with aOR = 1.95 (95% CI [1.4,2.7]; p < 0.001). Prescribing in this study was assessed using patients’ medical records; as prescriptions could not be reliably linked to individual prescribers, changes in individual prescribing behavior could not be evaluated. Conclusion This study demonstrated that smartphone technology can deliver antimicrobial prescribing guidelines in an LMIC like Laos. However, the trial did not demonstrate the pre-specified improvement in guidelines adherence with the smartphone app and AMS training compared with paper-based guidelines. While treatment guidelines underpin antimicrobial stewardship efforts, adherence depends on multiple factors beyond guideline availability. The trial was registered at clinicaltrials.gov (NCT04914793).